An Assessment of Decapod Crustaceans (Crabs and Shrimps) in Freshwater Riverine Systems across Watersheds of South-Central Guyana - Osborne, Chetwynd (International Journal of Scientific Research in Biological Sciences, 2021)
Areas across South-Central Guyana are very diverse and have the potential to sustain freshwater groups of vertebrates and invertebrates even though these areas are prone to major gold mining activities which have major impacts on the biodiversity both on land and in water. Some of the areas surveyed comprised of water bodies that were fully mined out and groups such as fishes, amphibians, insects, mollusks and crustaceans were the most representative animals. The knowledge of freshwater shrimps and crabs from Guyana is poor; hence the importance of this survey to identify the physicochemical parameters that serve as the best predictors of the density of crab and shrimps and examine the diversity trends using taxa abundance of crabs and shrimps. Water temperature (?) and dissolved oxygen (mg/l) seemed to be the best physicochemical parameters as it relates to predicting crustacean density and distribution across sites. River locality sites seem to have a stronger effect on crustacean community structure as compared to other surveyed localities (creek and waterfall), possibly indicating more suitable conditions within these sites. The number of five species of shrimps and four species of crabs was normal if we consider the range of area sampled.